An audit of children with Type 1 diabetes mellitus presenting to a tertiary institution in Johannesburg, South Africa - Gray, Meghann (My University, 2024)
At initial diagnosis, the rate of diabetes ketoacidosis (DKA) varies between countries (15- 67%) and may be associated with a lack of awareness of early signs and symptoms. Objectives: To describe the demographic, anthropometric, clinical and biochemical characteristics of children presenting with Type 1 diabetes mellitus (DM). Methods: A retrospective review of Type 1 DM children's medical records admitted to CHBAH from 01 January 2009 to 31 December 2018 was conducted. This ten-year period was further subdivided into two groups (Group 1: 2009-2013 (n = 75); Group 2: 2014-2018 (n=78)) to assess annual follow-up visit data in Group 1 for five years per patient and to compare data between the Group 1 and 2 time periods. Statistical differences between groups were analyzed by Mann-Whitney U test or Student t-tests, and for between the years of follow-up (Group 1), the paired student t-test was used. Results: The total number of newly diagnosed Type 1 DM children was 153. The median age at presentation was 10.5 years (IQR 7.4-12.3), 56% females and 88% black. The mean WAZ and HAZ were -0.8 (SD ± 1.5) and -0.4 (SD ± 1.6) respectively. Sixty-five percent (n = 100) presented in DKA, 56% of those being severe with a higher prevalence of DKA in group 2 compared to group 1 (72% vs 59%; p=0.08). At presentation, the median HbA1c was 12.5% (IQR 11.1-14.3) and C-peptide was 0.2ug/L (IQR 0.1-0.4) (normal range 1.1-1.4). Anti-GAD antibodies were positive in 82% (n=82/101) of the results available. In Group 1, HbA1c increased at year 3 follow up with advancing pubertal status. Despite changing to more intensive insulin therapy, mean HbA1c remained unchanged over the 5 years of follow-up. Conclusion: The majority of newly diagnosed children presented in severe DKA, similar to Red Cross War Memorial Children's Hospital (2005-2009), with an increasing prevalence over the ten vii years, which could be attributed to the lack of awareness of Type 1 DM in our population. An education campaign is needed to improve community knowledge about diabetes.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Diabetes; Awareness; Diabetes signs and symptoms; SDG-3: Good health and well-being